Participatory and localised climate and conflict risk assessments integrating peace and conflict analysis: Mapping and gap analysis - Josie Lianna Kaye; Ehmsen, Simon; Giorgia Nigatore; Han, Andreas Luis; Giulia Caroli (2022)
This mapping and gap analysis is produced by TrustWorks Global with Interpeace, with a view to informing the next steps of a process to develop a framework for conducting participatory and localised climate and conflict assessments that integrate peace and conflict analysis. It is designed to serve as a preliminary starting point for discussion and to foster a deeper, shared understanding of the most useful and, indeed, impactful ways to reach the objectives of the broader assignment of which this initial analysis forms a part.